Monoclonal antibody therapy for COVID-19 during pregnancy - Diana I. Abdulganieva; Ekaterina V. Dyakova; Era V. Ivanova; Nailya G. Shamsutdinova; Asiya R. Yangurazova; Nigina A. Nigmatullina; Ildar F. Fatkullin (Consilium Medicum, 2023)
Aim. Pregnancy worsens COVID-19 and has been listed by the US Food and Drug Administration as a high risk factor for complicating COVID-19. The severe course of a new coronavirus infection in some pregnant patients has created the prerequisites for the search for treatment methods that can reduce the likelihood of adverse outcomes. One of these therapy options is treatment with virus-neutralizing antibodies monoclonal antibodies. Experience with the use of monoclonal antibodies for the treatment of pregnant women is very limited, but in 2021 pregnancy was recognized as a high risk factor for the course of a new coronavirus infection, making it possible to use this group of drugs.